A review of pumped hydro energy storage. (25th March 2021) - Blakers, Andrew; Stocks, Matthew; Lu, Bin; Cheng, Cheng
Abstract: The need for storage in electricity systems is increasing because large amounts of variable solar and wind generation capacity are being deployed. About two thirds of net global annual power capacity additions are solar and wind. Pumped hydro energy storage (PHES) comprises about 96% of global storage power capacity and 99% of global storage energy volume. Batteries occupy most of the balance of the electricity storage market including utility, home and electric vehicle batteries. Batteries are rapidly falling in price and can compete with pumped hydro for short-term storage (minutes to hours). However, pumped hydro continues to be much cheaper for large-scale energy storage (several hours to weeks). Most existing pumped hydro storage is river-based in conjunction with hydroelectric generation. Water can be pumped from a lower to an upper reservoir during times of low demand and the stored energy can be recovered at a later time. In the future, the vast storage opportunities available in closed loop off-river pumped hydro systems will be utilized. In such systems water is cycled repeatedly between two closely spaced small reservoirs located away from a river. This review covers the technology, cost, environmental impacts and opportunities for PHES. The key motivations for this review are firstly that large amounts of variable wind and solar generators are being deployed; and secondly that there are vast opportunities for low-cost pumped hydro storage that do not require interference with rivers (with the associated environmental cost). Video Abstract: Video Abstract: A review of pumped hydro energy storage